Evaluation of four inch diameter VGF-Ge substrates used for manufacturing multi-junction solar cell - 曹可慰 刘彤 刘京明 谢辉 陶东言 赵有文 董志远 惠峰 (Journal of semiconductors, 2016)
Low dislocation density Ge wafers grown by a vertical gradient freeze（VGF） method used for the fabrication of multi-junction photovoltaic cells（MJC） have been studied by a whole wafer scale measurement of the lattice parameter,X-ray rocking curves,etch pit density（EPD）,impurities concentration,minority carrier lifetime and residual stress.Impurity content in the VGF-Ge wafers,including that of B,is quite low although B_2O_3 encapsulation is used in the growth process.An obvious difference exists across the whole wafer regarding the distribution of etch pit density,lattice parameter,full width at half maximum（FWHM） of the X-ray rocking curve and residual stress measured by Raman spectra.These are in contrast to a reference Ge substrate wafer grown by the Cz method.The influence of the VGF-Ge substrate on the performance of the MJC is analyzed and evaluated by a comparison of the statistical results of cell parameters.